THE RELATIONSHIP BETWEEN LEARNING MOTIVATION AND MATHEMATICS PROBLEM-SOLVING ABILITY OF SEVENTH-GRADE STUDENTS AT SMP NEGERI 1 SUSUA - Buulolo, Suci Murni Wartawati (Afore : Jurnal Pendidikan Matematika, 2024)
The aim of the research is to determine the relationship between learning motivation and the mathematical problem-solving ability of seventh-grade students at SMPN 1 Susua. The research approach is quantitative with a correlational research type. The population of this study consists of seventh-grade students at SMP Negeri 1 Susua, totaling 20 students, and the sampling technique used is total sampling. The instruments used are a mathematical problem-solving ability test and a questionnaire. Based on the research results, the value of tcount = 2.485813, was obtained, and to determine the ttable value with a 5% significance level, the value of rtable= 2.100922, was obtained. Therefore, since tcount = 2.485813 > ttable = 2.100922, it can be concluded that there is a relationship between motivation and mathematical problem-solving ability of seventh-grade students at SMP Negeri 1 Susua, with the level of correlation falling into the moderate category. Therefore, the researcher suggests that (1) students should have good learning motivation to achieve good mathematical problem-solving ability, (2) teachers should further develop good learning motivation to improve students' mathematical problem-solving ability, and (3) this study should be used as a comparison for future researchers and as a reference.